O NEOLIBERALISMO NO PARANÁ: UM RESGATE HISTÓRICO (Revista de História Regional, 2007)
This work presents some results of a researchwhich intended to follow the changes occurred in the politicaland economical options adopted by the members of thepolitical elite of Parana State during the 1980 and 1990decades and what was their position about the neoliberalideas which had been growing up in Brazil and in the worldfrom the second half of the 70s.